ANALYSIS AND INFLUENCE OF THE LEVEL OF INNOVATION & LEADERSHIP ON THE LEVEL OF ORGANIZATIONAL CHANGES - Momčilović, Oliver; Vujičić, Slađana; Doljanica, Dragan (Journal of process management and new technologies, 2022)
In order to improve both the internal and external functionality of the organization, organizational changes are increasingly sought. Changes are of great importance and without a doubt they are of crucial importance for strengthening and improving organizational efficiency. Organizational changes were always complemented by planned strategies and aligned with the organizational goal. The process of change is very challenging and important for organizations because it represents its path to success. Also, through organizational changes, organizations can be made capable of meeting future consumer demands and competing effectively with other market participants. However, many authors state that the changes are conditioned by a large number of factors. The aim of this paper is to examine the impact of leadership and innovation on the development of organizational changes in organizations in Serbia.